21st century literature from the Philippines and the world - Uychoco, Marikit Tara A., author (Manila : Rex Book Store, Inc., 2019)
21st century literature from the Philippines and the World explores literatures of the 21st century. It is divided into two parts: 21st century Philippine Literature and the 21st century world literature. It helps bridge the sstudent's knowledge on formalist literary perspectivess towards more post-colonial, socio-political perspectives about literature and society. Although the texts included have been published from 2000 and beyond, these span concerns about the new and the old. This book aims to help students understand the complexx world they live in through the use of literature.
Philippine history and literature -- Philippine realities -- Philippine diaspora -- Philippine speculative fiction -- World history and literature -- Real world issues -- World identities -- Specualtive fiction . Bibiliography -- index.
CORE-Kto12.
Includes bibliographical references and index.
In English text.
Keywords: Literature -- Problems and exercises; Literature -- Study and teaching